Efeito do método de preparação do catalisador na decomposição do metano - Drummond, Lorenna Magalhães (Universidade Federal de São Carlos, 2021)
The catalytic decomposition of methane reaction as is an alternative for the production of hydrogen and carbon nanomaterials, being considered a COx free route. The transition metals Ni, Fe, and Co are the most used as catalysts, pure or supported, in this reaction. The type of carbon formed in the reaction depends on the experimental conditions and the type of catalyst. Therefore, the objective of this work was to verify the influence of the catalyst preparation method on the production of hydrogen and carbon nanomaterials via methane decomposition. Ni catalysts supported on Al2O3, containing 10, 20, 30, 40, 60, 80 and 100% Ni, were prepared by coprecipitation and fusion methods. The catalysts and carbon nanomaterials were characterized by X-ray diffraction, scanning and transmission electron microscopy, Raman spectroscopy, nitrogen adsorption, reduction in the programmed temperature and thermogravimetric analysis. The catalytic reaction was carried out in a fixed bed reactor, at temperatures between 500 and 700 °C, atmospheric pressure, flow rates of 50 and 200 mL/min with 40% CH4 for 1 or 3 hours. The results of the characterizations suggest that materials prepared by the coprecipitation method have smaller particle sizes and, consequently, greater surface area. Both methods of preparation were efficient in the formation of carbon nanomaterials and the catalyst 80Ni-Cop had the highest amount of formed carbon, 8,67 gC/gcat, at 600 ºC with a flow rate of 200 mL/min. Considering the catalysts tested with a flow rate of 50 mL/min, 80Ni-Fus was the one with the highest formed carbon, 7,45 gC/gcat, at 600 ºC. The catalysts produced in this work and tested at DCM enabled the formation of carbon nanofibers that were later purified with HNO3. The purification was efficient in removing the Ni metal particles that were at the tip of the carbon nanomaterials (CNMs).
Effect of the catalyst preparation method on the decomposition of methane
Keywords: Catálise heterogênea; Decomposição do metano; Catalisadores de Ni; Nanotubos de carbono; Heterogeneous catalysis; Methane decomposition; Ni catalysts; Carbon nanotubes; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA